Estudo do calor de hidratação do concreto massa e contribuição ao cálculo térmico e à previsão de fissuras de retração - Gambale, Patrícia Guedes (2017)
The advancement of concrete technologies and methods of structural calculation nowadays makes buildings increasingly challenging, especially from the point of view of foundations. Foundation blocks with great volumes need attention as to the fissures arising from the exothermic process of hydration of the concrete, this concern defines the mixture as mass concrete, a widespread term in the construction of dams and that has been gaining space in urban civil construction. This study proposes the monitoring of prototypes of concrete blocks developed in the laboratory and foundation block in the field, with the use of thermocouples comparing with numerical methods of finite elements aiming to improve the prediction of cracks and to develop techniques so that they are avoided. This study will analyze the influence of the type and consumption of cement in the emergence of tensions arising from the energy released during its hydration. As results, a relation of the type interference and cement consumption is presented through the monitoring and analysis of the foundation block prototypes developed in the research, the development of a simplified unidirectional model of temperature and voltage prediction due to the heat of hydration for to evaluate the maximum temperature reached and the potential of cracking in the concrete mass and the comparison between the temperature results obtained in the Ansys program, which uses three- dimensional modeling and, as a way of validating the predictive model of thermal behavior as a reliable tool of analysis, the study also presents a field monitoring of a foundation block of a construction located in Goiânia and later application of the forecast model and the Ansys program. It was found, therefore, that the cement type has a considerable influence on the compressive strength and the adiabatic elevation, the latter being less significant. As for the cement consumption analysis, there was a notable increase in temperature in the concrete with higher consumption, causing cracks in the analyzed structure. By means of the results presented by the Ansys program, the monitoring of the prototypes and block in the field and the proposed forecast model, the validation of this model was confirmed as a good predictive tool of thermal behavior, highlighting some limiting conditions that surround it.